EVALUATION OF THROMBOCYTOPENIA, D-DIMER, INFLAMMATORY CRP, AND CBC MARKERS IN COVID-19 CASES, INCLUDING PATIENTS FROM IRAQ, USING A CASE-CONTROL METHODOLOGY - Younis Mosa , Nishtiman; Jassim Khalil, Dilan; Othman, Sameera A.; Abdo, Jasem M.; Othman, Adil A. (Science Journal of University of Zakho, 2024)
COVID-19 is a highly contagious viral illness caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). It primarily affects the respiratory system but can also impact other significant organs. Its rapid spread has heightened interest in biomarkers for screening and early diagnosis. This study evaluated D-dimer, C-reactive protein (CRP), and complete blood count (CBC) levels in patients with COVID-19 compared to healthy individuals. A total of 50 healthy individuals and 50 COVID-19 patients, aged 20 to 65, were included in the study, excluding individuals with conditions such as leukemia, thalassemia, or pregnancy. Whole blood and plasma samples were collected for CBC and D-dimer assays and stored at 2-4°C. The COVID-19 patients had significantly higher levels of D-dimer, CRP, white blood cells (WBC), granulocytes, and granulocyte percentage as compared with the healthy individuals (p<0.01), lower levels of lymphocyte percentage, mean corpuscular volume (MCV), and mean corpuscular hemoglobin (MCH) (p<0.01), as shown. The severe COVID-19 cases often show elevated D-dimer levels, indicating a higher risk of thrombosis. Increased CRP levels correlate with more severe conditions and help assess inflammation severity. A CBC provides insights into blood components, like RBC and WBC, and platelets. During COVID-19, CBC results may reveal lymphopenia, a low lymphocyte count linked to increased severity. For the most accurate and current information, consult healthcare professionals, reliable health organizations, or recent scientific studies on COVID-19.